Varying Chirality Across Nicotinic Acetylcholine Receptor Subtypes: Selective Binding of Quinuclidine Triazole Compounds - Jiradanai Sarasamkan (2018)
© 2016 American Chemical Society. The novel quinuclidine anti-1,2,3-triazole derivatives T1-T6 were designed based on the structure of QND8. The binding studies revealed that the stereochemistry at the C3 position of the quinuclidine scaffold plays an important role in the nAChR subtype selectivity. Whereas the (R)-enantiomers are selective to α7 over α4β2 (by factors of 44-225) and to a smaller degree over α3β4 (3-33), their (S)-counterparts prefer α3β4 over α4β2 (62-237) as well as over α7 (5-294). The (R)-derivatives were highly selective to α7 over α3β4 subtypes compared to (RS)- and (R)-QND8. The (S)-enantiomers are 5-10 times more selective to α4β2 than their (R) forms. The overall strongest affinity is observed for the (S)-enantiomer binding to α3β4 (Ki, 2.25-19.5 nM) followed by their (R)-counterpart binding to α7 (Ki, 22.5-117 nM), with a significantly weaker (S)-enantiomer binding to α4β2 (Ki, 414-1980 nM) still above the very weak respective (R)-analogue affinity (Ki, 5059-10436 nM).